Gómez de la Serna, Ramón. Buen Humor. Relatos ilustrados. Vitoria-Gasteiz: Sans Soleil Ediciones, 2020 [ISBN: 978-84-121578-5-7] - Laget, Laurie Anne (Eikón / Imago, 2022)
Reseña de la obra de Gómez de la Serna, Ramón. Buen Humor. Relatos ilustrados. Vitoria-Gasteiz: Sans Soleil Ediciones, 2020 [ISBN: 978-84-121578-5-7]